The EFFORTS TO IMPROVE CHILDREN'S MEMORY THROUGH GUESSING IMAGES USING ADOBE FLASH MEDIA - Utami, A A; Margaretha, L; Imran, R F (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to improve children's memory skills through a picture guessing game for group B children at PAUD Negeri Pembina 1 Bengkulu City. This research uses a type of classroom action research. As for the results of the study, it is known that from the results of class action research and discussion as described above, it can be concluded that the results of this study are that, using a guessing game can improve the memory skills of children aged 5-6 years in PAUD Negeri Pembina 1 Bengkulu City. This can be seen from an increase in children's memory in each cycle.